URGENSI PERSETUJUAN BAGI KEDUA CALON MEMPELAI DALAM PERKAWINAN - Ramadhan Syahmedi Siregar (Universitas Islam Negeri Sumatera Utara Medan, 2017)
Both the bride in marriage as well as approvalis very significant. So that Law No. 1 1974 and Law No. 39 of 1999 establishes in article Act as one condition of the validity of a marriage. If a marriage conducted without the consent of the andanya the bride, the marriage is not legal according to the laws that exist.